ANALISIS KETRAMPILAN GURU MATA PELAJARAN EKONOMI DALAM PENGELOLAAN KELAS PADA PEMBELAJARAN EKONOMI DI KELAS XI IPS SMA LABORATORIUM UM - Nur Fadhilatul Lailiyah; Sri Umi Mintarti (Jurnal Pendidikan Ekonomi, 2017)
Classroom management is very important since with a good class management teacher can control the teaching and leaning process even with some distractions. So the teaching and learning process can be effective and fulfill the aims that has been planed by the teacher. This study use descriptive qualitative method. The subject in this study are 11th grade economic teacher in SMA Laboratorium UM and students in 11th IPS grade. Data collection method use in this study are observation, interview, and documentation. Data analysis use in this study are data reduction, data display, conclusion and verification. The result of the study show that economic teachers’ classroom management skill in 11th IPS grade on SMA Laboratorium UM is good. Teacher is already well in conditioning the class. Teacher need more communicative in creating good communication with students. In managing classroom discussions teacher need to provide games and motivation to students. But, teacher need to be more assertive in reprimand and go around the class to control student behavior. DOI: https://dx.doi.org/10.17977/UM014v10i22017p173